2016
DOI: 10.4067/s0718-95162016005000053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of application of exogenous NO on the physiological characteristics of perennial ryegrass grown in Cd-contaminated soil

Abstract: A pot experiment was conducted to study the effects of sodium nitroprusside (SNP, a nitric oxide [NO] donor) on cadmium (Cd) toxicity in ryegrass plants. In the present study, ryegrass plants subjected to Cd toxicity were treated with different concentrations of SNP (50, 100, 300 and 500 µM), SNP solution was poured into Cdcontaminated soil every seven days. Cd treatment inhibited the plants growth and the absorption of micronutrients, increased accumulation of Cd in both shoots and roots. In Cd-treated plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…On the contrary to these elements, Ca concentrations in leaves were increased under Cd toxicity, which may be due to the fact that cell wall is the (Wang et al, 2016), and this study indicated that NO treatment induced the absorption of plasma membrane H + -ATPase activity under Cd toxicity ( Figure 5), which might be responsible for NO to adjust ion balance by increasing Fe, Cu, and…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the contrary to these elements, Ca concentrations in leaves were increased under Cd toxicity, which may be due to the fact that cell wall is the (Wang et al, 2016), and this study indicated that NO treatment induced the absorption of plasma membrane H + -ATPase activity under Cd toxicity ( Figure 5), which might be responsible for NO to adjust ion balance by increasing Fe, Cu, and…”
Section: Discussionmentioning
confidence: 78%
“…The level of lipid peroxidation in fresh leaf was measured in terms of malondialdehyde (MDA) concentration by the thiobarbituric acid reaction method (Wang et al, 2016). The MDA concentration was expressed as nmol g -1 DW.…”
Section: Determination Of Lipid Peroxidation and Soluble Proteinmentioning
confidence: 99%
“…A membrane fraction enriched in plasma membrane vesicles was prepared as described by Song et al ATP hydrolysis assays were performed as described by Wang et al (2016). 0.5 ml of the reaction medium con- .…”
Section: Determination Of H + -Atpase In Pmsmentioning
confidence: 99%
“…Muradoglu et al [ 48 ] found that supplementation of Cd increased K, Mg, Fe, Ca, Cu and Zn concentration in both roots and leaves of strawberry. Several studies, however, pointed to a decrease in the contents of mineral elements because of cadmium [ 54 , 55 , 56 , 57 ]. These inconsistent results are probably due to differences in the plant species, organs and/or assay methods used in various studies.…”
Section: Discussionmentioning
confidence: 99%